The impact of teaching by analogies in the collection of physics And the multiple intelligences of the class students scientific fifth (Journal of the College of Basic Education, 2023)
Numerous international, Arab and local studies and opinion polls have shown deficiencies in the teaching of physics until it was reflected in the difficulty of understanding it by students because it contains abstract concepts and various information related to all branches of physics, as studying this science requires the practice of thinking, the acquisition of physical knowledge and the production and application of that knowledge. In solving issues related to physical laws, making decisions about results, and solving life problems with natural phenomena and events(Dee & Zollman, 1997) quoting (Abdul Salam, 2006) believes that despite the importance of physics in bringing about scientific and technological progress and continuous development and its importance in the progress of peoples, many students do not accept its study and are alienated from it to the extent that they described the science of physics In (3D), namely: Difficult, Dul boring, Dislike repulsive.Both Biscone and Novak confirm that physics is one of the most difficult sciences for many students at the secondary level, and the Pre-University Education Committee in Mathematics and Science in the United States of America concluded that physics is difficult and that (84%) of American students do not accept this study. Science, and he adds (Abdul Salam, 2006) that the demand for scientific studies and the study of physics has become weak as a result of the low grades of students therein and because of the high school system and the lack of capabilities available in it. This is a common problem and is not limited to a particular country but includes other countries. (Abdul Salam, 2006:19)In Iraq, many studies have been conducted in the field of teaching physics, and different directions have been adopted, including the study of the misunderstanding of physical concepts and the development of appropriate solutions for them, and studies that dealt with the reasons for the low achievement and acquisition of physical concepts by students in different educational stages, and those studies reached the same previous result of having difficulty in The study of physics as a result of the use of traditional methods and methods that do not help the practice of thinking processes and the understanding of the expansion in the sciences of physics and in terms of its ability to organize and communicate a quantity of physical information in a functional way, such as the study of (Al-Shammari, 2002), (Al-Bawi and Thani, 2006) and (Al-Khazraji, 2008). (Al-Khafaji, 2008), (Damascus, 2009), (Muhammad, 2009), (Al-Zubaidi, 2010), (Al-Dujaili, 2010), and (Muhammad, 2010).